Contribución de la elaboración artesanal del Theobroma cacao L, cacao fino de aroma, al patrimonio cultural, en el cantón Vinces, provincia de los Ríos, Ecuador, año 2014 - Alvarado Barros, Karola Elizabeth (2014)
This research aims to highlight and promote the importance of the craftsmanship of fine cocoa aroma in canton Vinces, and show that this work is an important part of the ancestral wisdom traditions and practices that have become the people of that county especially farmers of the Corporation "La Pepa de Oro" so you need to recognize their work to go ahead, and is in this way that fair trade strategies were established to promote the value of handmade fine cocoa aroma. The methodology used in this thesis to describe the history and culture of fine cocoa aroma values involved collection of different literature sources obtained from books, dissertations, and internet, plus partners interviewed Corporation . To detail the processes of the products produced by the corporation spoke with women who do this work, then in order to observe and document procedures for each product and thus make the recipes and strategies for establishing meetings were held with business partners The work concludes that the fine cocoa aroma gathers historical and cultural values that are meaningful to the people of Canton Vinces, plus it is the result of organoleptic characteristics, which farmers give added value cocoa through its various derivatives produced by the traditional method, so strategies to preserve this cultural legacy established